Caeco‐caecal and caeco‐colic intussusception in two half‐sibling Standardbred horses. (3rd November 2019) - Gough, S. L.; Labens, R.; Quinn, C.; Hughes, K. J.; Slack‐Smith, V.; Hilbert, B. J.
Summary: This report describes caecal intussusception in two young half‐sibling Standardbred horses. Both horses presented showing signs of low‐grade abdominal pain. The horses remained haemodynamically stable despite signs of abdominal pain and associated tachycardia. Exploratory celiotomy was undertaken in both horses due to persistent abdominal pain and a poor response to administration of analgesic medications. Exploration of the abdomen revealed caeco‐caecal intussusception in one horse and caeco‐colic intussusception in the other horse. An underlying cause for caecal dysfunction and subsequent intussusception was not identified in either patient. Manual reduction of the intussusception was successful in both cases. The horses recovered uneventfully from surgery.